Asuhan keperawatan Dengan Pemberian Kompres Lidah Buaya (Aloe Vera L) Terhadap Penurunan Demam An. NA Di Desa Keliling Benteng Tengah Kecamatan Martapura Barat - Ferika Septarina; Eka Santi (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2022)
Children are an age group that is vulnerable to disease because their body systems are not yet perfect. Fever is a disorder that often occurs in children. Fever can have a negative impact that can harm children such as dehydration, lack of oxygen, neurological damage and febrile convulsions. Based on this, to minimize the negative impact, fever must be handled properly. One way of handling that is easy to do and obtain for children who have a fever is by applying a compress using Aloe Vera. The aim is to describe the effect of aloe vera compress on reducing fever in children. Descriptive observational method is a case study research design. The results obtained after the intervention of giving Aloe Vera L compresses for 15 minutes decreased the body temperature of children with fever. Aloe Vera compresses are proven to reduce the body temperature of children with fever because they contain lignin which functions as a heat absorber in the body and then transfers the heat to water molecules in aloe vera and can then lower body temperature. In addition, it contains saponins which vasodilate the skin, so that it will accelerate the way lignin works in lowering body temperature. The conclusion is, non-pharmacological therapy by giving Aloe Vera L compresses for 15 minutes can reduce the body temperature of children who have fever.